High strength and toughness of double physically cross‐linked hydrogels composed of polyvinyl alcohol and calcium alginate. Issue 10 (3rd November 2020) - Chen, Jiwei; Yang, Zhaokun; Shi, Dongjian; Zhou, Tianyang; Kaneko, Daisaku; Chen, Mingqing
Abstract: The weak mechanical properties of hydrogels, especially physically cross‐linked hydrogels are usually a major factor to hinder their application. To solve this problem, in this work, we prepared a high strength and toughness of double physically cross‐linked (PDN) hydrogels composed of crystalline domain cross‐linked polyvinyl alcohol (PVA) and Ca 2+ ‐cross‐linked alginate (Alg). With a further annealing treatment, the noncovalent cross‐linked network via the formed crystalline promote the as‐prepared PDN PVA/Alg hydrogel to exhibit well mechanical properties with the tensile strength of 1.94 MPa, elongation at break of 607% and Young's modulus of 0.45 MPa (above 70 wt% of water content). By analyzing the mechanism of improving the hydrogel mechanical properties, it is found that annealing can effectively improve the crystallinity of PVA in the hydrogel, and then greatly improve the mechanical properties of the hydrogel. This provides a general method for improving the mechanical properties of PVA PDN hydrogels. In addition, the PDN PVA/Alg hydrogel was also proved to have good ionic conductivity of 1.70 S m −1 . These desirable properties make the prepared physically cross‐linked hydrogels promising materials for medical and biosensing fields. Abstract :